Peningkatan Branding Produk Untuk Promosi UsahaMikro Kecil Menengah (UMKM) - Irwansyah; Muchamad Zainul Rohman; Wahyuni Eka Sari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The branding of a product or service is now more creative. One of them is using video. The right video can give potential buyers a positive perspective. However, there are obstacles in making attractive branding with videos, namely the ability to package attractive videos such as editing sound and images, dubbing and adding text. Another obstacle is the distribution of the video itself. Video creation sometimes requires applications with large resources. Meanwhile, as micro, small and medium enterprises (MSMEs), it is still rare to have computers with high enough specifications. As a solution to this problem, community service activities were carried out by the Samarinda State Polytechnic team to MSME owners in the city of Samarinda using the Kinemaster. The implementation of this activity is carried out for one day to meet face to face with online mentoring for one week. The method of implementation is carried out by lectures, practices, discussions and questions and answers. This intensive service was given to 35 participants. A total of 28 participants succeeded in making business product branding videos with a duration of 1 to 2 minutes